Development of Business Intelligence For Integration of Financial Reporting System In PT XYZ - Dea Carissa (Publikasi Indonesia, 2022)
The research aims to determine the relationship between two or more variables. Data collection with Literature and field research with questionnaires. The result of the research that is more influential in BAPPEDA Pemprov DKI Jakarta is the Business Intelligence variable, so it needs to be prioritized and given special attention to its implementation in the field. The research method used is associative research, designing Data Warehouse architecture, planning Data Warehouse sources, dimensional data modeling, filling in Data Warehouse. And the results of this study can be used as a reference for further follow-up with the DKI Jakarta Provincial Government BAPPEDA to be prioritized in the near future. The conclusion from the results of this study is that a transaction data warehouse designed using PDI (Pentaho Data Integration), is very helpful in collecting transaction data from original transaction data that already has a database and only as OLTP (Online Transactional Processing) data so that can be used as data OLAP. (Online Analysis Processing) so that it is analyzed using OLAP.